THE HUMANISTIC FORMATION AND THE UNIVERSITY STUDENTS’ HUMANIST - Hernández Infante, Rafael Carlos (2016)
University trains professionals who are able to face the challenges imposed on them, but this training should not focus only on the technical and scientific areas, it should include topics that are essential for the acquisition of a general culture. Higher education develops the processes of teaching, research and outreach, the latter one supported on cultural promotion, which influences the development of the students’ spirituality, as well as their personality. This article offers a proposal to favor the students’ humanistic training through the outreach process that takes place in the university educational project. In the preparation of this article, theoretical research methods have been employed, such as analysis and criticism of sources, and the hermeneutical method. Both methods foster interpretation and analysis of the study topic criteria, assessment and conclusions.